Implementation of Thyristor Based Control of Separately Excited DC Motor Driven by Single-Phase Semi-Converter - Diyoke, G. C.; Okeke, C. A.; Ezugwu, C. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This paper presents the implementation of thyristor-based control for a separately excited DC motor using a single-phase semi-converter. The study focuses on the design, operation, and performance analysis of the system, highlighting its ability to efficiently control the motor’s speed and torque. The semi-converter, consisting of thyristors, provides variable DC voltage to the motor by controlling the firing angle, enabling precise regulation of motor parameters. Key aspects, such as circuit design, firing angle control, and power quality considerations, are discussed in detail. Computer aided simulation results demonstrate the effectiveness of the proposed system in achieving smooth and reliable motor control with improved energy efficiency. The findings underline the applicability of thyristor-based control in industrial and automation applications, offering a cost-effective solution for DC motor drives. It is observed that the method of voltage control shows that a rated voltage of 200 V, the rated speed of 1500 RPM and torque of 10.5 N-m cannot be exceeded. The method of field flux control shows that a rated voltage, the rated speed can be exceeded to reach 208 V and 3000 RPM respectively while the rated torque cannot be reached.